PEMBENTUKAN KESADARAN KEBERSIHAN DIRI MELALUI KONSEP THAHARAH DALAM BUKU FIKIH MI KELAS I - Ala'ul Islam (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
Low personal hygiene awareness among elementary school students remains a persistent issue in Indonesia’s basic education context. This article aims to examine how the concept of thaharah in the Grade I MI Fiqh Textbook contributes to shaping hygiene awareness through value internalization, purification practices, and moral habituation. This study employs a library research method using literature documentation and thematic content analysis across four dimensions: thaharah as a foundation of hygiene character, its relation to moral behavior, the contribution of fiqh learning to hygienic habits such as handwashing, maintaining wudu, clothing and environmental cleanliness, and its alignment with character education principles. The findings indicate that thaharah is presented in concrete, visual, and practical forms, enabling students to understand cleanliness as part of their religious identity and personal responsibility. Practices such as wudu, istinja’, and hygiene etiquette strengthen discipline and establish sustainable hygienic routines grounded in spiritual values. The study concludes that integrating thaharah into MI fiqh instruction has strong potential to improve students’ hygiene culture by simultaneously nurturing religious values, hygienic behavior, and character formation.